From the Editor’s Desk - Alvita Nathaniel (Grounded Theory Review: An International Journal)
As with many aspects of life during the age of covid-19, the summer issue of the Grounded Theory Review has been delayed. We are pleased to publish, however late, this issue. The Grounded Theory Review is dedicated to supporting researchers who conduct classic grounded theory research. Classic grounded theory is a unique method of discovering never before recognized processes and patterns of human behavior, a method well-suited to studying current issues and processes.